CHARACTERISTICS OF INGREDIENTS OF MODERN OXIDATIVE HAIR DYES - SALEBA, LUDMILA; KANIVETS, ILLIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the current problem of the safety of using oxidative hair dyes, which occupy leading positions in the beauty industry and are in significant demand among consumers of different age and social groups. It was determined that the main factors of market development are the introduction of innovative technologies, the use of natural ingredients and the reduction of the content of aggressive synthetic substances. The purpose of the study is to analyze the chemical composition of hair colorants, assess their potential impact on hair and consumer health. Samples of dyes of the L’Oréal Paris, Schwarzkopf and Wella brands intended for permanent hair coloring were selected for the study. A detailed analysis of the composition of each product was carried out in accordance with the INCI labeling and the requirements of the Technical Regulations for Cosmetic Products of Ukraine (identical to Regulation (EC) No. 1223/2009). Oxidative hair dyes are multicomponent systems that contain demineralized water, solvents, emulsifiers, humectants, stabilizers, dyes, preservatives and aromatic additives. The main intermediates for the formation of a persistent dye (Toluene-2,5-diamine, m-Aminophenol, Resorcinol, 2,4-Diaminophenoxyethanol HCl) were identified, for which strict concentration limits (0.9–2.5%) were established. It was noted that these substances are potential sensitizers and can cause allergic reactions, dermatitis, skin irritation, and in some cases, mutagenic effects. The presence of components with conditioning and restorative properties, such as amino acids (arginine, lysine), moringa seed extract, and phospholipid complexes, was noted in the composition of hair dyes. It was concluded that further research should be aimed at optimizing hair dye formulations by reducing the content of potentially toxic components and searching for organic alternatives.